2022
DOI: 10.3390/nu14142971
|View full text |Cite
|
Sign up to set email alerts
|

A New Potential Dietary Approach to Supply Micronutrients to Physically Active People through Consumption of Biofortified Vegetables

Abstract: Micronutrients are required in many reactions involved in physical activity and exercise. Most physically active people do not meet the body’s needs in terms of micronutrients through diet. The novelty of the present manuscript is the use of an innovative dietary approach to supply micronutrients to physically active people through biofortified food. Therefore, the key point of this study was to verify whether supplementation with biofortified vegetables—and specifically molybdenum (Mo)-enriched lettuce—in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…We used a vegetable matrix (lettuce) as a carrier to supplement the diet with molybdenum. Our previous studies suggested a vegetable matrix was a good carrier for the mineral because the concentration of Mo was within the physiological range in serum and urine [ 28 ]. Thus, in the present study, we investigated the effect on bone metabolism and tested the effect with respect to a Molybdenum tablet supplementation group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a vegetable matrix (lettuce) as a carrier to supplement the diet with molybdenum. Our previous studies suggested a vegetable matrix was a good carrier for the mineral because the concentration of Mo was within the physiological range in serum and urine [ 28 ]. Thus, in the present study, we investigated the effect on bone metabolism and tested the effect with respect to a Molybdenum tablet supplementation group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we provided a quantity of molybdenum that was safe (in line with the biomonitoring equivalent values fixed to protect against deficits and nutritional toxicity, and very distant from 31 μg/L, which is the biomonitoring equivalent toxicity value reported for plasma and serum) [ 27 ]. The serum level of molybdenum was 5 μg/L at baseline [ 38 ] and reached 6 μg/L with the intake of 150 µg of sodium molybdate in tablet form [ 39 ] and 7 μg/L with the intake of biofortified lettuce for 12 days [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern consumers increasingly require food containing high amounts of macro- and micronutrients [ 1 , 42 , 43 ]. This need is linked to the lack of essential elements in human diets [ 23 , 44 , 45 ]. As a consequence, biofortification is recognized as a useful tool to enhance the concentration of trace elements, such as I [ 19 , 28 , 30 ], zinc [ 23 , 46 , 47 ], selenium [ 48 , 49 , 50 , 51 ], manganese [ 52 , 53 , 54 ], molybdenum [ 14 , 55 , 56 , 57 , 58 ], iron [ 59 , 60 , 61 ], and bioactive compounds in fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity is a key stimulus for symptoms management, it also produces lactate and myokines that contribute to brain health [ 11 , 12 , 13 ]. Several factors influence bone metabolism during physical activity, such as nutrition, as meals influence bone resorption through mechanisms still under study, such as the secretion of gut hormones [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. However, this mechanical stimulus must have a specific range within which the bone tissue response is activated, specifically from 50 to 100 microstrain (με), defined as minimum effective strain (MES) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%